2017
DOI: 10.1002/ejic.201700372
|View full text |Cite
|
Sign up to set email alerts
|

2,3‐Dihydro‐1H‐naphtho[1,8‐cd]borinine as a Potent Precursor for Open‐Shell Singlet B‐Heterocycles

Abstract: The reaction of naphthalene-1,8-diylbis[(trimethylsilyl)methanide] and dimethyl arylboronates afforded the corresponding 2,3-dihydro-1H-naphtho [1,8-cd]borinine as single dia- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The C-B bond lengths of species B are 1.535 Å and 1.543 Å, which is close to the 1.552 Å and 1.561 Å that were determined by X-ray crystallography. 14 A comparison of the calculated vibrational frequencies, intensities, and boron isotopic shifts with experimental observations are shown in Table 1, which are in excellent agreement. For species A, the observed 1544.8 cm À1 absorption is predicted at 1561.3 cm À1 without a boron isotopic shift.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…The C-B bond lengths of species B are 1.535 Å and 1.543 Å, which is close to the 1.552 Å and 1.561 Å that were determined by X-ray crystallography. 14 A comparison of the calculated vibrational frequencies, intensities, and boron isotopic shifts with experimental observations are shown in Table 1, which are in excellent agreement. For species A, the observed 1544.8 cm À1 absorption is predicted at 1561.3 cm À1 without a boron isotopic shift.…”
supporting
confidence: 64%
“…The C–B bond lengths of species B are 1.535 Å and 1.543 Å, which is close to the 1.552 Å and 1.561 Å that were determined by X-ray crystallography. 14…”
mentioning
confidence: 99%
“…As shown in Scheme 4 and eqn (1), the desired 6an could not be detected via the tBuOK-mediated reaction of 4t with 5a, and only acenaphthylene was generated in 42% yield along with the removal of two molecules of sulfinic acid salts. 17 The plausible mechanism pathways could include (1) tBuOK-mediated benzylic deprotonation of 4t, (2) intramolecular desulfonylative annulation by the resulting carbanion A1, (3) deprotonation of the in situ formed G by tBuOK, (4) proton exchange from the generated carbanion H to I, and (5) desulfonylative transformation from I to acenaphthylene. The results showed that the carbanion A1 preferred to yield the acenaphthylene byproduct via intramolecular double self-desulfonylation such that the following intermolecular condensation and ring closure pathway were a The reactions were run at the 1.0 mmol scale with 4 and 5 (0.5 equiv.…”
Section: Papermentioning
confidence: 99%